MENINGKATKAN MOTIVASI BELAJAR FISIKA SISWA MELALUI PENERAPAN STRATEGI PEMBELAJARAN TANDUR PADA KELAS X IIS4 LINTAS MINAT SMAN 12 PEKANBARU - Ridho, Afdhal Ridho; ', M. Rahmad; ', Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research aimed to describe the level of students motivation in temperature and heatmaterial through the implementation of TANDUR learning strategy in class X IIS4 SMAN 12 Pekanbaru. Problem derived based on the observation of the students in class X IIS4 SMAN 12 Pekanbaru, showed low motivation. Of learning it is shown in the proces of learning, where the students give less attention to the lesson, students are less enthusiastic in learning physics and students physics learning outcomes are still low are still low. To improv student motivation required appropiate learning strategy, one of the main strategies that can be used is TANDUR which is an acronim of grow, natural, name, demonstration, repeat, celebrate. Through TANDUR learning strategies expected to be fully able to make the students motivated to learn physics especially in the subject of temperature and heat, and provide direct experience to the students and try to give a real experience for them, so itâ€™s not just memorize facts, but they themselves are finding the facts. This study used a form of pre-experimental design with one group pretets-posttest design. Instrument which is used in this study is the motivation questionnare consisting of aspects of attention, relevance, confidence, and satisfaction. Data were analyzed using descriptive analysis. Based on the results of the research, students motivation after the application of TANDUR learning strategy increased 2,88%. Thus the implementation of learning strategies in the class X IIS4 SMAN 12 Pekanbaru can increase students motivation to learn physics in the temperature and heat subject. Key Words : the TANDUR learning strategy, student motivation, temperature and heat subject. Â